(3QSGdI JSgjd GdaMU Yf QhGjI GdEeGe MaUs
(3ChdgG (B:s
(3hHYO bO SFdJ bHd GdBf Cf CaQO QhGjI GdEeGe GdeTghQ HGdGJbGf CYfj CHG YeQh MaU s
(3BNQgG (B:s
(3hGdajd hGdcGaQhf hGdchKQ hGdfUQ hGdadb hGdfGSJeJ gPg GdfSNI GdoeHGQcI HMeO Gddg hYhfg s
(3YdjgG hba ddLGeY GdCRgQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs